Phenotypic and genetic correlations in Musa populations in Nigeria - Tenkouano, A.; Ortíz, R.; Baiyeri, K. (African Journals Online, 2002)
Breeding efforts for genetic improvement of banana and plantain have gradually shifted from individual trait selection to simultaneous improvement of several traits, following an ideotype concept. Therefore, information on the phenotypic and genetic association among these traits, and the influence of environmental factors thereupon, would be valuable to the Musa breeder. In this regard, the correlation of several traits with bunch weight was assessed for a sample of 36 Musa genotypes grown at three locations (Abuja, Ibadan and Onne) for two consecutive crop cycles. Genetic correlations between bunch weight and plant height at flowering, height of the tallest sucker at maturity of mother plant and number of days for fruit filling were smaller than phenotypic correlations, suggesting a synergistic effect of genotypes and environments on phenotypic relationship between bunch weight and those traits. However, the genetic correlations between bunch weight and the number of days to flowering or the number of leaves was higher than phenotypic correlations. The associations between bunch weight and yield components were higher than between bunch weight and phenological traits. In the former cases, the genetic correlation was similar to the phenotypic correlation, indicating that the effect of genotype x environment interaction on the relationship between bunch weight and yield components was neutral. This indicates that yield components could serve as indirect selection criteria for yield. Generally, there was a higher genetic expression for most yield components during the second crop cycle in all the environments. This probably implies that selection should be carried out in the second crop cycle. Different correlations were observed across locations, suggesting that different selection indices may be constructed to identify ideotypes best suited to specific agro-ecological niches.